Economic and environmental analysis of plastics pyrolysis after secondary sortation of mixed plastic waste. (15th January 2023) - Kulas, Daniel G.; Zolghadr, Ali; Chaudhari, Utkarsh S.; Shonnard, David R.
Abstract: Plastic usage has quickly grown in recent years as plastics have become an essential material in everyday life. Unfortunately, recycling rates have not matched the increased growth, with the majority of waste plastic currently landfilled in the United States. New chemical recycling technologies, i.e. pyrolysis, are needed to increase the recycling rates of waste plastics. However, pyrolysis is challenged with bridging of feed into the hot reactor and in the high cost of waste plastic feedstock. In this work a novel liquid-fed pyrolysis process, designed to eliminate bridging, was modeled through process simulation and assessed over a range of processing conditions. A secondary sortation of inexpensive mixed plastic waste from material recovery facilities provided a low-cost feedstock (PE, PP) for pyrolysis. A techno-economic analysis and life cycle assessment found favorable economic and environmental results for pyrolysis oil when compared to fossil naphtha ($561/t, 0.52 kg CO2 eq./kg). A sensitivity analysis found the economic results most responsive to waste plastics feedstock costs, pyrolysis gas sales, operating capacity, and waste disposal costs. Furthermore, it is recommended to recover and sell sorted PET from the mixed plastic bale and implement heat integration in pyrolysis, which in our study achieved lower minimum selling price and greenhouse gas emissions for pyrolysis oil then for fossil naphtha. Graphical abstract: Image 1 Highlights: Novel liquid-fed plastics pyrolysis applied to produce synthetic naphtha. Secondary sortation of mixed plastic waste enables chemical recycling. Identified sustainable processing conditions through robust scenario analyses. Most favorable parameters achieve a 10x reduction in minimum selling price. 5x reduction in greenhouse gas emissions achieved compared to fossil naphtha.